PAIN MANAGEMENT IN THE ELDERLY WITH NON-PHARMACOLOGICAL TECHNIQUE: KINESIOTAPING - Achmad Syukkur; Febrina Secsaria Handini (Jurnal Keperawatan Malang, 2022)
Background: As the final stage of the life cycle, old age is a normal developmental stage and a gradual process of changes, including physical, social and psychological changes. One of the complaints caused by physical changes in older adults is pain. The more common pain in older adults is musculoskeletal pain. There are two commonly used pain management, namely, pharmacological and non-pharmacological therapy. One of the non-pharmacological techniques that can be used to reduce pain in the elderly is the use of kinesio plasters or kinesio taping. Purpose: The purpose of this study was to determine the effect of kinesio taping as a non-pharmacological pain management technique on pain in the elderly. Methods: This study uses a quantitative method of Quasi Experiment through a Pretest-Posttest approach with Control Group Design, with a sample of 28 respondents who were taken using a simple random sampling technique. The questionnaire in this study used the Visual Analog Scale (VAS) application on an android smartphone. Result: There was a difference in pain before and after kinesiotaping in the intervention group with a p-value <0.05 using the paired sample t-test, and there was a difference in pain between the intervention group and the control group, with a p-value <0.05 using the independent t test. -test. Conclusion: Pain management, especially non-pharmacological in the elderly, is very prioritized to avoid the use of pharmacological therapy in the long term. One alternative non-pharmacological therapy that can be implemented is kinesiotaping.